EVALUATION OF THE TUBERCULOSIS SURVEILLANCE SYSTEM IN CRISTINO CASTRO-PI - Lopes dos Santos , Samuel; Marinho Campelo, Cassio (Cadernos ESP, 2025)
Objective: To evaluate the tuberculosis surveillance system in the municipality of Cristino Castro - PI, from 2019 to 2023. Methods: This is a descriptive, retrospective study using secondary data from the SINAN system, which was assessed for data quality attributes (completeness and consistency) and representativeness. Results: 20 tuberculosis records were analyzed, with 7 variables classified as excellent (completeness) and 3 relationships between variables classified as excellent (consistency). The surveillance system was considered adequate and rated excellent (representativeness). The epidemiological profile was of men aged between 35 and 49 and the majority of cases were new admissions. HIV testing was low (55%) for individuals with TB. Conclusion: The quality of the data for the TB surveillance system in the municipality of Cristino Castro-PI was considered excellent. The system was considered representative when analyzing the epidemiological variable of person.